Computer department students use smart phones in the educational process Field study at the Higher Institute of Science and Technology – Al-Kufra - karbaj, Mousa Muhammed Omar; jaber, Garber khalfa (Journal of Pure & Applied Sciences, 2021)
This study aimed at using of smart phones in education as one of the new forms of education, and as a result of the great scientific and technological revolution, it was necessary for university institutions to follow the electronic curriculum and use modern educational media. Smart phones are one of these means and their use in the educational process, in addition to knowing the degree of using smart phones in the educational process for students at Computer Department at the Higher Institute of Science and Technology in Kufra. The descriptive analytical method was used in the study, by distributing questionnaires to all members of the study community from the students at computer department and surveying them during the academic year 2020/2021. The total number of questionnaires rose to (85) questionnaires. The results of the study showed high percentages in the use of smart phones due to the ease of use at any time and place without any difficulties. The smart phones are present with students constantly, and this enhances the fact that the use of smart phones in education develops the cognitive aspect, and research skills. The study recommended that the need to conduct training courses for both students and faculty members to employ and use applications of mobile learning in a way that serves the educational process and build learning systems based on the mobile environment. As well as the need to reconsider the programs and curricula and their implementation strategies to continue assimilating the concepts of the electronic and technological revolution with pace, while conducting more studies that reveal mobile learning applications in other stages of study.